Optical properties of Ag doped Bi2WO6 nanoplates synthesized by hydrothermal process - Phuruangrat A. (National Institute R and D of Materials Physics, 2015)
© 2015, Inst Materials Physics. All rights reserved. In this research, 0, 1 and 3 mol % Ag doped Bi2WO6 crystalline products were synthesized by hydrothermal process. The effects of Ag dopant on the structural and optical properties were studied by an X-ray diffractometer (XRD), a transmission electron microscope (TEM), an X-ray photoelectron spectroscopy (XPS) analyzer and a UV-visible spectrometer. The XRD patterns were specified as crystalline structure of Russellite Bi2WO6. TEM images revealed the presence of the products in the shape of nanoplates. The Bi2WO6 and 3 mol % Ag doped Bi2WO6 show strong absorption in the visible light region with the energy gaps of 3.34 and 3.42 eV, respectively.